Experiences of mental health help-seeking among students utilising Mental Health - Rathebe, Puleng (My University, 2021)
Due to academic pressures, financial difficulties and other challenges of emerging adulthood, South African university students are experiencing higher rates of mental health problems. Research indicates a significant prevalence of stress, anxiety and depression among university students. There has also been an increase in suicides among the South African student population. Despite these challenges, help-seeking for mental health problems is still relatively low among this group. The aim of the current study was to explore the experiences of mental health help-seeking among students utilising mental health services at the University of the Witwatersrand. The study was conducted in order to understand help-seeking from students’ perspective. Individual interviews were conducted on a sample of eleven full-time students between the ages of eighteen and twenty-five. The data was analysed using the descriptive phenomenological method. The findings suggest that students seem to have adequate mental knowledge regarding the recognition of mental health concerns and information about accessing care which is imperative for help-seeking. However, students’ expectations about psychological treatment did not match their actual experiences which may indicated misconceptions about what treatment entailed. Stigma seems to influence help-seeking intentions, although it did not prevent actual help-seeking behaviour. A greater sense of belonging and shared experiences among the students regarding mental health difficulties were experienced as promoting help-seeking behaviour and preventing perceived public stigma
A research report is submitted in partial fulfilment of the requirements for the degree of Master’s in Community-Based Counselling Psychology in the Faculty of Humanities at the University of the Witwatersrand, 2021